Atividade biológica de timbó (Lonchocarpus floribundus) sobre carrapato bovino - Machado, Aaron Ferreira (2012)
The tick Rhipicephalus (Boophilus) microplus is the most important ectoparasite national livestock. This mite cause large economic losses, estimated to be about two billion dollars, to the Brazilian livestock. The aim of this work was to evaluate the biological activity of ethyl acetate, ethanol and aqueous extracts of Lonchocarpus floribundus roots on catte tick R. (B.) microplus. To evaluate the acaricidal activity on engorged females were collected adults ticks in cattle artificially infested. The ticks were separated into groups of ten individuals, weighed and immersed in L. floribundus roots extracts at concentrations of 5, 25, 50, 75 and 100 mg.ml-1 for five minutes. For the evaluation larvae, individuals were used from 14 to 21 days, which were immersed in the extracts at concentrations of 1, 5, 10, 15 and 20 mg.ml-1. After treatment each group was placed in incubator B.O.D. at 27 ± 1 °C a nd relative humidity of 80 ± 5%. Engorged females and larvae mortality rates were evaluated for six days and 24 hours respectively. Oviposition rates were evaluated over fifteenth day after the treatments. Reproductive efficiency and control of reproduction were evaluated over fifteenth day after weighing eggs. The experiment was completely randomized with five treatments, five replicates and a control group. The data were analyzed by analysis of variance (ANOVA) followed by Tukey test (P < 0.05). The extracts evaluated were not toxic enough to induce mortality of engorged females over 50%. The ethyl acetate and ethanol extracts induced 100% mortality of larvae. However for values of median lethal concentration (LC50), the ethanol extract (LC50 = 2.13 mg.ml-1) was more toxic than the ethyl acetate extract (LC50 = 4.09 mg.ml-1). The ethanol extract estimated IC50 of 3.03 mg.ml- 1 and it was more toxic than the other extracts on this parameter. Among the three extracts evaluated, the ethyl acetate and ethanol extracts showed the best results for the control of reproduction of R. (B.) microplus, reaching 100% at concentration of 5 mg.ml-1. The L.floribundus roots extracts showed biological activity on cattle tick. Keywords: Vegetable extracts, tick, engorged females, mite, Boophilus.